Knowledge mapping and research trends of IL-33 from 2004 to 2022: a bibliometric analysis - Jin, Jingyi; Wan, Yantong; Shu, Qiang; Liu, Jinghua; Lai, Dengming (Frontiers in Immunology, 2023)
Background IL-33 has been studied widely but its comprehensive and systematic bibliometric analysis is yet available. The present study is to summarize the research progress of IL-33 through bibliometric analysis. Methods The publications related to IL-33 were identified and selected from the Web of Science Core Collection (WoSCC) database on 7 December 2022. The downloaded data was analyzed with bibliometric package in R software. CiteSpace and VOSviewer were used to conduct IL-33 bibliometric and knowledge mapping analysis. Results From 1 January 2004 to 7 December 2022, 4711 articles on IL-33 research published in 1009 academic journals by 24652 authors in 483 institutions from 89 countries were identified. The number of articles had grown steadily over this period. The United States of America(USA) and China are the major contributors in the field of research while University of Tokyo and University of Glasgow are the most active institutions. The most prolific journal is Frontiers in Immunology, while the Journal of Immunity is the top 1 co-cited journal. Andrew N. J. Mckenzie published the most significant number of articles and Jochen Schmitz was co-cited most. The major fields of these publications are immunology, cell biology, and biochemistry & molecular biology. After analysis, the high-frequency keywords of IL-33 research related to molecular biology (sST2, IL-1), immunological effects (type 2 immunity, Th2 cells), and diseases (asthma, cancer, cardiovascular diseases). Among these, the involvement of IL-33 in the regulation of type 2 inflammation has strong research potential and is a current research hotspot. Conclusion The present study quantifies and identifies the current research status and trends of IL-33 using bibliometric and knowledge mapping analysis. This study may offer the direction of IL-33-related research for scholars.